Kelly papers. - Victoria. Public Record Office (Melbourne : Public Record Office, 1980)
Collection of extracts from some of the official papers.
Murder of police : notice of withdrawal of reward --Kelly's last letter -- Kelly's career.
Caption title.
Keywords: Kelly, Ned, -- 1855-1880.